Implementation of school-based curriculum as perceived by secondary school teachers of English - Diem, Chuzaimah D.; Yusfardiyah, Yusfardiyah; Koniaturrohmah, Binti; Lismalayani, Lismalayani (Universitas Pendidikan Indonesia, 2016)
Information about Curriculum 2013 has seemed to make many EFL teachers feel anxious. This anxiety is assumed to happen due to the unwillingness of the teachers to implement the new curriculum because they have not yet even implemented the previous curriculum (KTSP) in their classrooms optimally. This study was aimed primarily at investigating the implementation of KTSP covering three important components: preparation, application, and evaluation by 107 secondary school teachers of English. To collect the data, â€œKTSP Implementation Questionnaireâ€ was used. The data collected based on the teachersâ€™ own perceptions were analyzed in relation to their education level, teaching experience, certification status, and KTSP socialization involvement. The results showed that (1) 62% teachers confessed that they had not yet optimally implemented KTSP although all of them had been involved in its dissemination program done by the government; (2) there was no correlation between either education level or teaching experience and the implementation of KTSP. However, (3) there was a significant correlation between teachersâ€™ certification status and their (i) KTSP preparation, (ii) teaching experience, and (iii) involvement in dissemination program activities.